2009
DOI: 10.1016/j.jacc.2009.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Computed Tomography Angiography for Early Triage of Patients With Acute Chest Pain

Abstract: Objectives To determine the usefulness of coronary computed tomography angiography (CTA) in patients with acute chest pain. Background Triage of chest pain patients in the emergency department (ED) remains challenging. Methods Observational cohort study in chest pain patients with normal initial troponin and non-ischemic electrocardiogram. 64-slice coronary CTA was performed prior to admission to detect coronary plaque and stenosis (>50% luminal narrowing). Results were not disclosed. Endpoints were acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(148 citation statements)
references
References 45 publications
7
139
0
2
Order By: Relevance
“…The ROMICAT study was a study of CCTA in low-risk patients admitted with chext pain, in which all subjects received CCTA; the results were not provided to clinicians and did not influence in-patient management decisions. 31,32 The Institutional Review Board of Partners Health Care approved the study. Patients provided written consent, and the consent of providers answering our research questionnaire was implicit.…”
Section: Methodsmentioning
confidence: 99%
“…The ROMICAT study was a study of CCTA in low-risk patients admitted with chext pain, in which all subjects received CCTA; the results were not provided to clinicians and did not influence in-patient management decisions. 31,32 The Institutional Review Board of Partners Health Care approved the study. Patients provided written consent, and the consent of providers answering our research questionnaire was implicit.…”
Section: Methodsmentioning
confidence: 99%
“…Adipose tissue area ranged from K250 to K50 HU. The mid-thigh skeletal muscle area was compartmentalized into areas of normal-density muscle (C31 to C100 HU) and low-density muscle (0 to C30 HU) (13).…”
Section: Quantification Of Regional Fatmentioning
confidence: 99%
“…The study showed an excellent NPV (98%) of significant stenosis for exclusion of ACS, but a low PPV (35%), since approximately 50% of patients with obstructive CAD or inconclusive assessment at cardiac CT were finally diagnosed with ACS. 70 Furthermore, the limited sensitivity owing to a number of patients who were false negative (77%, n 5 7 of 31) may be explained by the limited accuracy of cardiac CT to detect stenosis in small-calibre vessels (,2 mm); rupture or thrombosis in subcritical CAD or microvascular disease. 70 However, the excellent NPV (.98%) was uniformly demonstrated in most of the series evaluating population with ACP.…”
Section: Cardiac Ctmentioning
confidence: 99%
“…70 Furthermore, the limited sensitivity owing to a number of patients who were false negative (77%, n 5 7 of 31) may be explained by the limited accuracy of cardiac CT to detect stenosis in small-calibre vessels (,2 mm); rupture or thrombosis in subcritical CAD or microvascular disease. 70 However, the excellent NPV (.98%) was uniformly demonstrated in most of the series evaluating population with ACP. A study including nearly 600 patients at ED with low risk (TIMI risk score 0-2), of whom 84% patients were discharge based on a negative cardiac CT, likewise demonstrated a NPV of 100% for adverse events within 30 days.…”
Section: Cardiac Ctmentioning
confidence: 99%
See 1 more Smart Citation